The development of paediatric Malay matrix sentence test (PaedMalayMST) materials through the construction of a paediatric Malay corpus - Zakaria, Nur 'Azzah; Jamaluddin, Saiful Adli; Wan Ahmad, Wan Aslynn Salwani; O'Beirne, Greg A.; Zulkeflee, Nur Awatif; Abd Razak, Atiffah (University of Malaya, 2022)
The selection of material is important in the development of a paediatric speech perception test. Even though several studies have documented various sources of speech testing materials, using corpus was recommended to develop a Matrix Sentence Test (MST). However, as available Malay corpus was limited to written words only, this research aims to construct a Paediatric Malay corpus from a combination of written and spoken words of children in Malaysia and to develop word-based matrix (WBM) for the Paediatric Malay Matrix Sentence Test (PaedMalayMST) based on the developed corpus. The WBM replicates the Malay grammatical structure in these three categories: number, object, and adjective. Based on these criteria, the words from the developed corpus were then filtered by considering the frequency of occurrences and its phonemic distributions to be included in the WBM. As a result, a matrix of three categories with six words for each category was constructed.